Sosialisasi Peningkatan Motivasi Kewirausahaan Pelajar Dalam Mendukung Potensi Pertumbuhan Ekonomi Lokal - Muhammad Rizky Ramadhan (LP3M INSTITUT KH YAZID KARIMULLAH, 2024)
This Real Work Lecture (KKN) program was carried out by students of the Muhammadiyah University of North Sumatra in Telaga Pure Village, Langkat Regency. This activity focuses on increasing student motivation in entrepreneurship to encourage local economic development. Through this service, students help and provide education to the community on the importance of having a strategy in entrepreneurship, especially students. The main aim of this activity is to increase awareness and motivation of the community and students about the importance of entrepreneurship to boost local economic development. This program consists of several activities, outreach and mutual cooperation activities to maintain a clean environment. The results of this activity show increased motivation and awareness in the student generation and also new knowledge for society. Apart from that, students also succeeded in motivating residents to be more active in protecting the environment and increasing awareness of the importance of health.